PERBANDINGAN VOLUME DAN MASSA NUTRIEN OPTIMUM PADA KARAKTERISTIK KIMIA NATA DE LERI DARI LIMBAH AIR CUCIAN BERAS - Wahab, Hasmawati; Ahmadi, Ahmadi; Hulyadi, Hulyadi (Hydrogen: Jurnal Kependidikan Kimia, 2016)
In the processing of rice into the rice used is rice that has been whased away, while the rice water thrown away because it was considered important that the rice water that is not used will be waste, it is necessary alternative in their utilization. The alternative is to make a food product by a fermentation process using bacteria Acetobacterxylinum called nata de leri. It is caused rice water contain nutrients such as carbohydrates, protein, and vitamin B1 or thiamine. This study aimed to compare the volume and optimum mass of nutrients at chemical characteristicts of nata de leri generated. This type of research was Pre-Experimental by varying nutrient source used was suger as a carbon source and tofu waste water as a source of nitrogen. In this research, was adding four variations of nutrient source that has been 100:25 (g/mL), 125:50 (g/mL), 150:75 (g/mL), 175:100 (g/mL). Furthermore, the analisisproksimat include moisture content, ash content, fat content, protein content, and carbohydrate content. Best treatment combination was obtained on the addition of nutrient source 125:50 (g/mL) which generate 78,7217% moisture content, ash content of 1,0707%, fat content of 0,5636%, protein content of 0,4776% and the carbohydrate content 19,1893%.